Corynelia oreophila (Speg.) Starb. en el Noroeste Argentino - Catania, Myriam del Valle (Lilloa, 2004)
Se describe e ilustra Corynelia oreophila (Speg.) Starb. y algunos estadios de la colonización de la hoja.